Corrosion non-uniformity of steel bars and reliability of corroded RC beams. (15th July 2018) - Gu, Xianglin; Guo, Hongyuan; Zhou, Binbin; Zhang, Weiping; Jiang, Chao
Highlights: A new model was created to measure the non-uniform corrosion factor R . The critical value of factor R is used to predict failure mode in corroded rebars. New non-uniform corrosion factor R was used to analyze reliability of RC beams. Abstract: To study the non-uniform distribution of cross-sectional areas and mechanical properties of corroded steel bars under a chloride environment, 19 concrete slabs embedded with steel bars were exposed to a chloride environment to achieve accelerated corrosion. A 3D measurement technique was employed to create geometric models of corroded steel bars, and their cross-sectional areas of a corroded steel bar, a probability distribution model of the spatial variability factor R, was developed through signal processing and statistical analysis methods. The R factor is the ratio of the average cross-sectional area to the minimum one and was applied to analyze the mechanical behavior response to the non-uniform corrosion of steel bars under tensile loading. In addition, the relationship between the mechanical properties and R factor of a corroded steel bar was established to predict its critical state of brittle failure. Our novel approach to this analysis enabled the calculation of the time-dependent reliability of a simply supported corroded reinforced concrete beam. The results showed that non-uniform corrosion is the critical factor affecting the time-dependent reliability of a reinforced concrete beam; moreover, changes in the failure mode of a corroded steel bar may severely impair the reliability of a reinforced concrete beam.